Teachers’ Role in Enhancing Students’ Literacy and Numeracy: A Qualitative Case Study at SDN Sambiroto Rembang - Dwi Hajar Fitri Astuti; Titik Haryati; Sumarno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe the role of teachers in improving students’ literacy and numeracy at SDN Sambiroto Rembang. This research employed a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The research subjects included classroom teachers, the principal, and students. The findings reveal that teachers play a significant and multifaceted role in enhancing students’ literacy and numeracy skills. These roles include being educators, instructors, coaches, and assessors. As educators, teachers instill learning values and shape students’ character. As instructors, they apply active, contextual, and collaborative learning strategies. As coaches, they provide structured guidance and continuous practice that improve students’ thinking skills and comprehension. As assessors, teachers utilize formative and diagnostic assessments to guide appropriate instructional interventions. These findings suggest that a holistic and reflective teaching role greatly contributes to building a strong foundation of literacy and numeracy from early educational levels.